Integrated Flow Chamber System for Live Cell Microscopy - Kriesi, Carlo; Steinert, Martin; Marmaras, Anastasios; Danzer, Claudia; Meskenaite, Virginia; Kurtcuoglu, Vartan (Frontiers in Bioengineering and Biotechnology, 2019)
In vitro quantification of the effect of mechanical loads on cells by live microscopy requires precise control of load and culture environment. Corresponding systems are often bulky, their setup and maintenance are time consuming, or the cell yield is low. Here, we show the design and initial testing of a new cell culture system that fits on standard light microscope stages. Based on the parallel plate principle, the system allows for live microscopy of cells exposed to flow-induced shear stress, features short setup time and requires little user interaction. An integrated feedback-controlled heater and a bubble trap enable long observation times. The key design feature is the possibility for quick exchange of the cultured cells. We present first test results that focus on verifying the robustness, biocompatibility, and ease of use of the device.